Front‐line nurses' perceptions of intra‐hospital handover. Issue 13 (4th March 2020) - Tobiano, Georgia; Ting, Christine; Ryan, Christine; Jenkinson, Kim; Scott, Lucie; Marshall, Andrea P.
Abstract: Aim and objective: To explore nurses' perceptions of factors that help or hinder intra‐hospital handover. Background: Miscommunication during clinical handover is a leading cause of clinical incidents in hospitals. Intra‐hospital nursing handover between the emergency department and inpatient unit is particularly complex. Design: A descriptive, qualitative study. This research adheres to the consolidated criteria for reporting qualitative research. Methods: Forty‐nine nurses participated in group interviews, which were analysed using inductive content analysis. Results: Three categories emerged: (a) "lacking clear responsibilities for who provides handover"; (b) "strategies to ensure continuity of information"; and (c) "strained relationships during handover." Conclusions: Intra‐hospital handover requires clear processes, to promote high‐quality information sharing. Ensuring these processes are broad and acceptable across units may ensure nurses' needs are met. Relational continuity between nurses is an important consideration when improving intra‐hospital handover. Relevance to clinical practice: Nursing managers are optimally positioned to enhance intra‐hospital handover, by liaising and enforcing standardisation of processes across units. Nurse managers could promote intra‐unit activities that foster front‐line nurses' communication with each other, to encourage problem‐solving and partnerships.